Exploring Development Challenges in Uganda Using Modernization Theory - Nambassa, Gloria; Purnomo, Eko Priyo (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
This paper explores challenges of modernization theory in Uganda by analyzing its conceptual distinctions and theoretical frameworks. Modernization theories are typically categorized into 'critical variable' and 'dichotomous' approaches, each defining modernization through specific social changes or the acquisition of modern attributes by traditional societies. Drawing on works by theorists like Schwartz and Levy, the critique examines how these frameworks inadequately capture Uganda's complex modernization realities. The study aims to provide a nuanced understanding of modernization's applicability to Uganda's development trajectory. Methodologically, it employs a comprehensive review of scholarly literature and theoretical analysis. The findings underscore the limitations of prevailing modernization theories in explaining Uganda's development and suggest implications for policy and practice. This analysis contributes to ongoing debates on development theories and their relevance in diverse global contexts, advocating for more context-sensitive approaches to understanding and promoting socio-economic progress in Uganda.